Intermedial Turn in Goethe’s Novel “The Sorrows of Young Werther”: from Sentimental Literary Centrism to the Musicalization of Literature - Bentia, Iuliia (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
The relevance of the study The publication in 1774 of the epistolary novel by Johann Wolfgang von Goethe became not only an outstanding fact in the biography of a still very young German genius at that time. The echoes of this event can be felt over the next several years, when this work literally turned the worldview of contemporaries, as well as in the following centuries in numerous artistic paraphrases. Obviously, the meaning of The Sorrows of Young Werther goes far beyond the purely literary sphere; therefore, its research should be approached with the appropriate tools. This key can be intermediality, which explores the processes of interspecific interaction of arts as mediums that do not compete with each other, do not strive for mutual intervention, but, on the contrary, reinforce each other’s action. The study of the mechanisms of intermediality makes it possible to go beyond the narrow professional field and determine the general cultural context of the era, which is an urgent task of modern humanitarian science. The purpose of the study is to characterize the mechanisms of interaction between literature and music in Goethe’s epistolary novel The Sorrows of Young Werther and the basic role of these mechanisms in the formation of a sentimentalist worldview. The results and conclusions. Consideration of the Goethe’s epistolary novel The Sorrows of Young Werther in the aspect of intermedial connections prompts several thoughts at the same time. First, in this novel, at the declarative level, literature retains its position as an already fully formed social institution. Literature, like art history and philosophy, is not anonymous here, but personified. In this approach, one senses an attempt at an aesthetic discussion with immediate contemporaries, the penetration of a publicistic component into a work of art, which became a powerful part of Herder’s essay sermons in the late 1760s. At the same time, music and painting appear as forms of realizing the ‘true,’ extremely sensual human nature, not reduced by various secular conventions. Werther draws, Charlotte plays the piano and sings, the ball scene is permeated with music. The newfangled hobby for folklore has determined the anonymity of musical toposes in the novel: these are ancient songs that sound accompanied by a piano, as well as popular dances—in this one can also see the influence of J. G. Herder. The entire fabric of the novel permeates and defines music as a super-idea: the music of the language and the music of novel drama with its discontinuous fragmentation and temporal fluidity. The presence of music within the story legitimizes its emotional exaltation, unpredictable syntax. The mention of singing or playing music influences the development of the storyline, the music becomes that invisible director who constructs the form of a whole literary work. The intermedial interaction of the two by nature temporal arts serves as an intensified catalyst for the ‘feelings biography’ of the protagonist, which also unfolds in time and directs the reader’s attention to the irrational sphere. The interpenetration of literature and music becomes a tool for overcoming outdated artistic conventions and the formation of a new type of European literature, in which attention to the sensual sphere becomes a way of reflecting the life of the New Age as fluid, subject to constant changes. The main conclusion of the study is that The Sorrows of Young Werther marks a turn from the typical for sentimentalist style music ‘literaturezation’ to counter processes, which will be fully revealed already in the era of romanticism.